Implementation of E-Archives at the Faculty of Communication and Information Technology Using the Web-Based Waterfall Method - Rafif Ramadhan Al Yarda; Iskandar Fitri; Benrahman (Institute of Computer Science (IOCS), 2021)
Information technology is currently developing rapidly so that every aspect of activity cannot be separated from the name technology, of course in the administrative aspect it also really requires fast and accurate information technology. At the Faculty of Communication and Information Technology, National University, currently still using an archive system that has not been developed again, which often causes data synchronization. With the E-Archives application, it is hoped that archiving activities can assist administrative activities accurately so that it can become a reference in making the right decisions